2016
DOI: 10.1007/s40726-016-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on VOC Emissions from Automobile Sources by Means of Online Mass Spectrometry

Abstract: This study reviews recent research on volatile organic compound (VOC) emissions from motorized vehicle sources by means of online mass spectrometry. Chemical ionization is a powerful tool that usually permits soft ionization of chemical species and it allows the time-resolved measurement of multiple VOCs, even in complex samples where many kinds of VOCs coexist. The vehicular exhaust gasses are investigated using H 3 O + , NO + , Hg + , and CH 3 C(O)O − as a reagent ion in online chemical ionization mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…NACs (Inomata et al, 2016;Perrone et al, 2014;Le Breton et al, 2019). BB is considered a major driver of atmospheric NAC formation (Kahnt et al, 2013;Laskin et al, 2015) because the combustion of coal and wood, which leads to causes thermal degradation and pyrolysis of lignins, results to strong emission https://doi.org/10.5194/acp-2020-899 Preprint.…”
Section: Introductionmentioning
confidence: 99%
“…NACs (Inomata et al, 2016;Perrone et al, 2014;Le Breton et al, 2019). BB is considered a major driver of atmospheric NAC formation (Kahnt et al, 2013;Laskin et al, 2015) because the combustion of coal and wood, which leads to causes thermal degradation and pyrolysis of lignins, results to strong emission https://doi.org/10.5194/acp-2020-899 Preprint.…”
Section: Introductionmentioning
confidence: 99%
“…An array of instruments was used to characterize gas-and particulate-phase pollutants inside the 6-m 3 FBC. Gas-phase organic species were measured with two proton transfer reaction mass spectrometers (PTR-MS, Ionicon), as detailed in our previous studies 50,51 The data shown in this study were obtained in the 6-m 3 FBC. The ratio of the CO concentration in the 30-m 3 EDC and 6-m 3 FBC (i.e., chambers before and after passage through the pumps, respectively) was 0.183; the corresponding ratio of the THC concentrations was 0.194.…”
Section: Methodsmentioning
confidence: 99%
“…An array of instruments was used to characterize gas-and particulate-phase pollutants inside the 6 m 3 FBC. Gas-phase organic species were measured with two proton transfer reaction mass spectrometers (PTR-MS, Ionicon), as detailed in our previous studies 50,51 and Section S1 of the ESI. † The detection sensitivities are listed in Tables S1-S3 of the ESI.…”
Section: Methodsmentioning
confidence: 99%
“…Within this scenario, a critical role is played by the possibility of reducing weight [3], saving energy [4], abating chemical [5] and acoustic [6] emissions. A large number of subsystems are potentially involved: engines, aerodynamic shapes, gearboxes, cockpit, control unit settings, seals (for sound and water insulation), and so on.…”
Section: Introductionmentioning
confidence: 99%